The virtual portfolio as a pedagogical evaluation instrument in Ecuador. Valuations from the teaching act - Briceño-Núñez, Chess E. (2021)
This research shows a study of teacher appreciation on the effectiveness of the virtual portfolio as an instrument of pedagogical evaluation in Ecuador. The study had the sample participation of 100 teachers in active practice, belonging to the Basic General Education Level, in the Coast-Galapagos region, during the first five-month period of the 2020-2021 school year. Participants were selected by intentional sampling and under informed consent. The instrument applied is a decimal scale test to measure the perception of evaluation instruments, with a total of ten propositions, each one with possible variations ranging from a minimum score of 1 to a maximum score of 10 for each proposed assertion, which Its purpose was to identify the degree of validity of this strategy. The results show that in the opinion of teachers the virtual portfolio is a highly effective tool in pedagogical evaluation, so the study concludes that its application in the educational context as a pedagogical tool is relevant and effective.